Assessment of Research Quality of Telehealth Trials in Pain Management: A Meta‐Analysis. Issue 5 (27th September 2012) - McGeary, Donald D.; McGeary, Cindy A.; Gatchel, Robert J.; Allison, Sybil; Hersh, Allison
Abstract Although telehealth‐based pain management research has grown over the last decade, it is difficult to determine the state of the research because of methodological differences and variability in quality among existing studies. In a previous systematic review, we outlined these differences and preliminarily explored the promise of telehealth for pain intervention. We completed a PRISMA compliant meta‐analysis of telehealth pain management research to more precisely describe the state of the research and to uncover gaps in the existing literature that highlight directions for future research. We identified 10 relevant studies completed between 2000 and 2011 including 3 noninferiority and 7 superiority studies. Meta‐analysis revealed an overall benefit of telehealth interventions over control conditions and equivalence with in‐person intervention. However, some of the reviewed studies found no benefit for telehealth over control conditions. Some methodological concerns among the examined research included poor research quality, small sample sizes, and the examination of telehealth pain interventions without proven efficacy for in‐person treatment. Recommendations for future studies are reviewed.